2020
DOI: 10.1002/app.49853
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the mechanical and dielectric responses in polymer films by a fractional calculus approach

Abstract: A fractional calculus approach was used to study the correlation between the complex elastic modulus and the complex relative permittivity for a polystyrene (PS) film with thickness of ~80 μm. Experimental measurements were carried out using dynamic mechanical analysis and dynamic dielectric analysis. Experimental results show the mechanical and dielectric manifestations of the main relaxation (glass transition process), whose molecular mobility was analyzed by two innovative models: a mechanical fractional mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 21 publications
3
18
0
1
Order By: Relevance
“…In recent research, Renteri ́a-Baltieŕrez et al employed a fractional correlation model to establish a connection between the mechanical and dielectric responses of α-relaxation in polyvinyl butyral 18 and polystyrene. 19 The results showed that the parameters from the fractional models demonstrated a direct proportionality between the temperature and molecular mobility. In this way, the correlation model successfully related the mechanical and dielectric properties of polymers.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In recent research, Renteri ́a-Baltieŕrez et al employed a fractional correlation model to establish a connection between the mechanical and dielectric responses of α-relaxation in polyvinyl butyral 18 and polystyrene. 19 The results showed that the parameters from the fractional models demonstrated a direct proportionality between the temperature and molecular mobility. In this way, the correlation model successfully related the mechanical and dielectric properties of polymers.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, the relaxation times, mechanical or electrical, for cooperative motions, τ cooperative , is given by the following law in a temperature range T 0 < T < T*. 19 Ä…”
Section: Correlation Between Dielectric and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Чаще и проще проводить анализ полимеров экспериментальным путем, что, как правило, сопровождается использованием дорогостоящей техники и достаточно масштабного и затратного технологического процесса. Таким образом объясняется актуальность использования неэмпирических методов на основе математических, информационных и химических подходов, а именно их прогностическая функция [2][3][4].…”
Section: Introductionunclassified
“…In the literature, an interesting topic is to find the correlation between viscoelastic and dielectric responses [19], both of which can be regarded as intermediate states. The mechanical characterization of viscoelasticity lies between pure elasticity and viscosity, which are the zero-and first-order derivatives of the strain rate.…”
Section: Introductionmentioning
confidence: 99%